Rosa machailensis (Rosaceae), a new species from Jammu and Kashmir, India - Singh, Kanwaljeet; Singh, Harsh; Sharma, Yash Pal; Gairola, Sumeet (Phytotaxa, 2022)
The new species Rosa machailensis from Paddar subdivision of Jammu &Kashmir is described and illustrated. It is closely allied to Rosa moschata but differs in having acute leaflet, densely glandular margins and long auriculate stipules, broad prickle base, emarginate, mucronate and incised petals, small size of hips (pseudo fruit), thick exine of pollen and broad grooves on exine surface.